ANALISIS DAN EKSPERIMEN BLANK HOLDER GAP MINIMUM PADA PROSES RECTANGULAR CUP DEEP DRAWING - Susila Candra; I Made Londen Batan; Wajan Berata; Agus Sigit Pramono (Teknoin, 2016)
This paper aims to investigate the magnitude of minimum blank holder gap to prevent wrinkles and cracks defects of the rectangular cup with T4 material Tin Plate CA. Punch-die domensions are determined based on the standard tool designed. The methods of this research are an analytic, finite element (FE), and experimental approach, respectively. Each method in this study had been mutually compared to other methods. According to the research, minimum blank holder gap is recommended by 120% to 130% of the thickness of the initial material (about 0.24 ÷ 0.26 mm). By using the value of this gap, the height of wrinkles is very small, and the magnitude of the drawing force is still below the critical limit, so the product does not occur wrinkles and cracks.